Model penerapan elemen Siger pada fasade dan lingkungan arsitektural di Bandar Lampung - Novrizal Primayudha; Detty Fitriany (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2019)
The Indonesian architectural city growth and development are strongly influenced by their heterogenity of sociocultural lives. each region produces various cultural artifacts that traditionally accommodate cultural concepts and noble values in every social activity and environmental arrangement around it. . This existence makes all provinces and regions of Indonesia have a distinctive building typology as a regional symbol that will be found at the region. The Bandar Lampung City Government has a special policy in managing city architecture by applying its cultural artifacts to every architectural environment and fostering it as a concept of regional cultural signs and symbols. Siger is one of the various regional sign concepts that emerge as an architectural sign on public buildings and their built environment in Bandar Lampung City. The implementation this concept is done with a variety of shapes and sizes that greatly affect the architectural form of the building. This inequality needs to be systematically facilitated through the search of scientific design and architecture to produce an ideal application model. This research was conducted using qualitative ethnographic research methods with analysis based on participant descriptive and argumentative observation. The study aims to identify siger as a sign of culture and reveal the relationship of application to the facade of public building architecture, through the classification of buildings. Furthermore, the design concept and the application model of Siger will be used as a proposal for the city government in managing the order of the architecture facade of public buildings and their environment in a sustainable manner.  Key words: architecture of Bandar Lampung City, Siger, model of architectural facade management